Influence of e-counseling skills on counseling self-efficacy among e-counselors in Malaysia - Zainudin, Zaida Nor; Rong, Lee Wei; Asri, Alia Sarah; Yusop, Yusni Mohamad; Ahmad, Nor Aniza; Hassan, Siti Aishah (Society for Research and Knowledge Management, 2022)
Despite the rise in e-counseling services in Malaysia, there is an apparent lack of studies conducted from e-counselors’ perspectives on e-counseling features and provisions. The aim of the study is to determine the relationship between e-counseling skills and counseling self-efficacy. This quantitative study applied the descriptive correlational method in order to identify the relationship between e-counseling skills and counseling self-efficacy among e-counselors. The instrumentation involved the use of the Counseling Self-Estimate Inventory (COSE) and a self-constructed questionnaire, the E-Counseling Skills Scale which has undergone validity tests. 233 e-counselors from various institutions in Malaysia were selected using the simple random sampling technique to participate in completing an online survey form. Findings showed that respondents reported a high level of e-counseling skills (M = 4.07, SD = 0.60) and a moderate level of counseling self-efficacy (M = 4.00, SD = 0.67). E-counseling skills was positively correlated with counseling self-efficacy (r = .421, p < .05). The multiple regression analysis reported that the subconstruct “goal identification and attainment” of e-counseling skills best predicted counseling self-efficacy (β = .27, t(225) = 2.33, p .05). The findings implied that a higher ability to apply e-counseling skills is linked to higher counseling self-efficacy among e-counselors in Malaysia. This study suggests further improvement and standardization in the counselor education and training policy, specifically in terms of e-counseling interventions for both professional counselors and counseling trainees.